Pemberdayaan dan usaha peningkatan ekonomi suku Talang Mamak di kawasan Taman Nasional Bukit Tiga Puluh melalui budidaya Kelulut (Heterotrigona itama) - Avry Pribadi; Andhika Silva Yunianto; Nur Hajjah; Fonda Amelia Sarah (Unri Conference Series: Community Engagement, 2020)
Bukit Tiga Puluh National Park is not only a place for wildlife but also a home for Talang Mamak tribe (a local and native tribe lives inside the National Park). Furthermore, to support Talang Mamak, an empowerment is critically needed. Meliponiculture is one form of empowerment activity provided by Thirty Hills National Park. There are many steps to do this empowerment activities, namely, conducting preliminary survey, forming groups for each sub villages, training, giving grant beekeeping equipments, assistance, detailing in marketing, and evaluating. Results showed that in the first year after training, honey production increased 85.5% in the third quarter compare to honey produced in the second quarter. Other groups, such as KTH Batu Berdiri and KTH JelemuBengayuan, also gave similar tendency. These results also revealed that the empowerment activity by doing meliponiculture had given positive contribution for Talang Mamak even though it`s production is still not much. Nevertheless, there are some obstacles when doing this meliponiculture. For instances, sometimes, Talang Mamak people is less focus when facing problems. Other problems are that they cannot determine their market target and there is no maintenance toward the stingless bees’ colonies.